Mitigation of Damage in the Context of Remedies for Breach of Contract - Michaud, Anne (Revue générale de droit, 1984)
When I began this article my main objective was to show why the concept of mitigation of damage, which is so extensively used in common law, was apparently non-existent in civil law. Right from the beginning, however, I found conclusive evidence which proved that the concept of mitigation actually exists in civil law too; my purpose was then transformed into explaining how this concept works in two systems of law that are so different in their approaches and their methodologies. In order to make this study manageable, I have focused on the links between the concept of mitigation and the problem of pecuniary loss following a breach of contract. Consequently, issues pertaining to tort, physical injuries to persons and things, and claims to liquidate sums, as in debt, will be dealt with only incidentally. Regrettably, this course of action will leave open many interesting questions related to mitigation, mainly in tort but also in contract. Nevertheless, I trust that the present study will constitute a useful basis for further analysis on this subject. I have divided this work into two parts, devoted to the two phases of recovery following a breach of contract. The first phase concerns the choice of which losses fall under the protection of the law, among all those claimed by the plaintiff. I propose to call this phase measuring the extent of the loss. The second phase involves the determination of what the defendant will have to do in order to compensate the plaintiff; when this compensation takes a pecuniary form it involves the assessment of the pecuniary value of the loss. The first of these phases primarily concerns the extent of losses and the question of what damage counts for compensation; this particular aspect of the issue of mitigation is the subject of Part I of this article. The connection between mitigation and the pecuniary evaluation of a plaintiff's damages is examined in Part II where I focus on the effects of inflation and other factors that influence the cost of compensation. Finally, from a comparative point of view, one of the main interests of the present study lies in observing that the concept of mitigation has achieved a different status in civil law and in common law. The conclusion of this work explores this situation, and aims at explaining the historical and juridical circumstances that may have caused common law to attain higher levels of generality and of abstraction than civil law with regard to the issue of mitigation.